Relevance Versus Irrelevance of Scientific Research Skills to the Practice of the Accounting Profession - Lilia Grigoroi; Cristina Mihaela Lazar; Svetlana Mihaila (Ovidius University Annals: Economic Sciences Series, 2024)
Assessing the relevance of scientific accounting research to the practice of the profession is a topic less present in the literature, and the results of empirical research are often divided. In this context, the research aims to analyse the extent to which scientific accounting research is necessary and relevant for the practice of the profession. The views and opinions presented in this paper will represent the author's perceptions of students' and practitioners' attitudes towards indigenous accounting research, formed both from an academic perspective and from the perspective of the practicing accountant.